THU0146 Dispensing of Biologics Prescribed for the Treatment of Rheumatoid Arthritis in the Australian Population. (9th June 2015) - Jones, G.; Bird, P.; Hall, S.; Littlejohn, G.; Tymms, K.; Youssef, P.; Chung, E.; Bennett, C.; Button, P.
Abstract : Background: Current guidelines for rheumatoid arthritis (RA) recommend starting a biologic DMARD in combination with methotrexate (MTX) in patients responding insufficiently to MTX and/or other synthetic disease modifying anti-rheumatic drugs (DMARDs) with or without glucocorticoids. There is limited data on drug survival studying all modes of action in the same population. Objectives: The primary objective was to describe the persistence on biologic (b) DMARDS in the Australian landscape. The secondary objectives were to investigate the influence of MTX and other DMARD concomitant medications, effect of patient age at initiation and bDMARD treatment line on biologic persistence. Methods: RA patients aged ≥18 for whom biologics were dispensed for their RA and who were in the Australian Medicare 10% sample database (dating from 01 August 2010 to 31 June 2014) provided by the Department of Health and Aging through an Australian healthcare consulting company (PROSPECTION) were included in the study. The following bDMARDS were included abatacept (ABA), adalimumab, certolizumab pegol, etanercept, golimumab, infliximab (INF) and tocilizumab (TCZ). The duration of treatment was determined for each treatment regimen. Data were analysed using descriptive statistics for continuous variables and frequency counts for categorical variables. Time-to endpoints was summarised using Kaplan-Meier (K-M) methodology. Individual sub-cutaneous (SC) anti-TNFs were equivalent in all analyses and therefore were combined for simplicity. Results: Data from 1230 patients were included in the analysis; 27% were ≥65 years old and 73% were between 18-64 years old. The majority (73%) were females. For all patients, the percentage (based on K-M estimates) who continued on treatment at 6 months (mo) after commencement was 84% for TCZ, 75% for ABA, 69% for SC anti-TNFs and 40% for INF. Median time to stopping treatment was 39 mo (95% CI:29-ND) for TCZ, 32 mo (95% CI:19-ND) for ABA; 21 mo (95% Cl:17-26) for SC anti-TNF, and 3 mo (95% CI:1-12) for INF. Longer median treatment persistence was observed for concomitant SC anti-TNFs and ABA with MTX or other DMARDs than for monotherapy (but not TCZ; Table 1 ). Age was not associated with treatment persistence. Significant differences were observed for treatment line and persistence (Table 2 ). Conclusions: As first line therapy, ABA and possibly TCZ (p=0.08) have superior persistence compared to SC anti-TNFs. For second line, TCZ was superior to all other options and, for third line, none were different but this was hampered by small numbers. MTX and other DMARDs improve persistence for ABA and SC anti-TNF but not TCZ. These real world data help inform clinicians about choice of therapy at initiation and the use of concomitant DMARDs. Acknowledgements: The study was sponsored by Roche Products, Pty, Limited. Medical writing was provided by Dr Joseline Ojaimi from Roche. Disclosure of Interest: G. Jones: None declared, P. Bird: None declared, S. Hall: None declared, G. Littlejohn: None declared, K. Tymms: None declared, P. Youssef: None declared, E. Chung Consultant for: Roche Products Pty Limited, C. Bennett Employee of: Roche Products Pty Limited, P. Button Employee of: Roche Products Pty Limited